Metode Pembelajaran Bahasa Arab Bagi Anak Usia Dini (Studi Kasus Di Paud Darul Ulum Pao Prenduan Sumenep) - Ainul Yakin; Uzlifatul Jannah; Achmad Syarif Fathoni (Dirosat : Journal of Islamic Studies, 2020)
The existence of Early Childhood Education Institutions (PAUD) in Indonesia is very important in order to optimize the stimulation of development, especially motor, cognitive and language development from an early age so that children can grow and develop optimally. PAUD institution is an institution that provides care, education and development services for children aged 0 -72 months. This is equally important in the process of learning activities carried out by the teacher in internalizing a value with teaching materials that have been prepared beforehand. So, the teacher as an educator as well as a teacher must be innovative and creative in finding learning methods including learning Arabic that he does.The focus of this research is to learn how to learn Arabic for young people at the Darul Ulum Pao Prenduan Sumenep PAUD Institute and want to find out what learning methods are used by teachers and their application in the teaching and learning process.In this study the authors used a qualitative research approach with a descriptive-analytic method. There are two sources of research data, primary data that researchers get from school principals, teachers and students. While the secondary data are several documents that are already in the Institute. The data analysis technique uses a single case design with the data analysis model introduced by Miles and Hiberman, namely the data analysis process is carried out starting from the process of data collection, presentation and verification or drawing conclusions. The conclusion that can be drawn is that there are several Arabic language learning methods used by teachers in early childhood at the Darul Ulum Pao Prenduan PAUD institution, namely language learning using various methods. In learning Arabic, sometimes the teacher uses the rote method, sometimes uses the game method, and also the singing method. the three methods used have been running smoothly and according to what is stated in the teaching theory.